Anti-falling antibacterial foaming insole as well as preparation method and application thereof

By adding components such as hydroxyl-containing polyquaternary ammonium salt, hydroxyethyl acrylate grafted EVA and terminal isocyanate polyurethane to the EVA insole material, a chemical crosslinking system is formed, which solves the problem of insufficient strength and antibacterial properties of traditional EVA insole material, and improves the The toughness and hydrophilicity of the material are enhanced and anti-slip and fall resistance is enhanced.

CN119119628AActive Publication Date: 2024-12-13KUNSHAN FIRST PEOPLES HOSPITAL

Patent Information

Application Number
CN202411270925.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

Traditional EVA insole materials have insufficient strength, toughness, antibacterial and mildew resistance, and have poor hydrophilicity, which affects its application effect.

Method used

The chemical crosslinking hybrid system is formed through high-temperature kneading and molding to improve the compatibility, strength and hydrophilicity of the materials. And set dot protrusion matrix on the surface to enhance friction.

Benefits of technology

It significantly improves the tear strength, tensile strength and elongation of break of EVA insole material, improves moisture absorption and moisture absorption performance, and significantly enhances antibacterial and mildew resistance, and improves anti-slip and anti-fall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005038672940000021
    Figure BDA0005038672940000021
  • Figure BDA0005038672940000022
    Figure BDA0005038672940000022
  • Figure BDA0005038672940000081
    Figure BDA0005038672940000081
Patent Text Reader

Abstract

The invention relates to the technical field of EVA (ethylene vinyl acetate), and discloses a drop-resistant antibacterial foaming insole as well as a preparation method and application thereof, the foaming insole is prepared from the following components in parts by weight: 100 parts of ethylene-vinyl acetate copolymer, 1-8 parts of hydroxyl-containing polyquaternium, 0.6-5 parts of hydroxyethyl acrylate grafted EVA, 0.8-7 parts of isocyanate-terminated polyurethane, 4-5.5 parts of foaming agent and 0.8-1.5 parts of assistant, 1.2 to 1.7 parts of a cross-linking agent; in the high-temperature mixing and mold pressing process, hydroxyl groups of the hydroxyl-containing polyquaternium and the hydroxyethyl acrylate grafted EVA react with isocyanate-terminated groups of the polyurethane, so that the hydroxyl-containing polyquaternium, the hydroxyethyl acrylate grafted EVA and the isocyanate-terminated groups of the polyurethane form a chemical cross-linked hybrid system, and the insole material shows higher tear strength, tensile strength and elongation at break; meanwhile, good hydrophilicity and antibacterial and mildew-proof performance are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of EVA, in particular to a fall-proof and antibacterial foam insole and a preparation method and application thereof. Background Art

[0002] Ethylene-vinyl acetate copolymer (EVA) is a general-purpose polymer with good elasticity, flexibility, glossiness and low cost. It is widely used in the shoe industry, such as soles and insoles. Improving its mechanical properties such as strength and toughness can make EVA have better practical applications in materials such as insoles. Traditional EVA insoles have poor hydrophilic and moisture absorption properties, poor moisture permeability, and are prone to mold and bacteria during long-term wear, which poses safety and health problems.

[0003] Quaternary ammonium salt macromolecular polymer has good antibacterial properties, and good heat resistance, is not easy to decompose, and is widely used in polymer materials. Patent CN118006032B discloses using quaternary ammonium salt chitosan, polyvinyl alcohol, tetraethyl orthosilicate, coupling agent etc. as raw materials, prepares composite antibacterial agent, mixes with EVA resin plastic matrix, EVA-g-MAH compatibilizer, obtains plastic injection molding with antibacterial property. But this EVA plastic injection molding does not have good hydrophilicity, is unfavorable for the practical application of EVA in hydrophilic breathable insole. Summary of the invention

[0004] The technical problem solved by the invention is to improve the mechanical strength, antibacterial and mildew-proof performance and hydrophilicity of the EVA foam insole material.

[0005] The technical solution of the present invention is a fall-proof and antibacterial foam insole, which comprises the following components in parts by weight: 100 parts of ethylene-vinyl acetate copolymer, 1-8 parts of hydroxyl-containing polyquaternary ammonium salt, 0.6-5 parts of hydroxyethyl acrylate grafted EVA, 0.8-7 parts of terminal isocyanate polyurethane, 4-5.5 parts of foaming agent, 0.8-1.5 parts of auxiliary agent, and 1.2-1.7 parts of cross-linking agent.

[0006] Preferably, the preparation method of the hydroxyl-containing polyquaternary ammonium salt comprises: adding 1,3-dichloro-2-propanol and N,N-bis[2-(dimethylamino)ethyl]terephthalamide in a molar ratio of 1:(0.8-1.2) to isopropanol, stirring and condensing and refluxing at a temperature of 80-85°C for 48-60h, rotary evaporating the solution, washing with acetone, and drying to obtain the hydroxyl-containing polyquaternary ammonium salt. The reaction formula is as follows:

[0007]

[0008] Preferably, the preparation method of N,N-bis[2-(dimethylamino)ethyl]terephthalamide comprises: adding terephthaloyl chloride, N,N-dimethylethylenediamine, and pyridine in a molar ratio of 1:(1.8-2.2):(2-2.2) to tetrahydrofuran, stirring and reacting at room temperature for 6-10 hours, rotary evaporating the solution, separating by silica gel column chromatography, and eluting with a solution of ethyl acetate and petroleum ether to obtain N,N-bis[2-(dimethylamino)ethyl]terephthalamide. The reaction formula is as follows:

[0009]

[0010] Preferably, the preparation method of the isocyanate-terminated polyurethane comprises: drying and removing water from polyethylene glycol, then mixing it with diisocyanate in a molar ratio of 1:(2.1-2.2), reacting at 65-70° C. for 2-3 hours in a nitrogen atmosphere, and cooling to obtain the isocyanate-terminated polyurethane.

[0011] Preferably, the diisocyanate is isophorone diisocyanate, toluene-2,4-diisocyanate or diphenylmethane-4,4'-diisocyanate.

[0012] Preferably, the foaming agent is azodicarbonamide and the cross-linking agent is dicumyl peroxide.

[0013] Preferably, the auxiliary agent includes zinc stearate, stearic acid or a combination thereof.

[0014] Preferably, the preparation method of hydroxyethyl acrylate grafted EVA comprises: mixing ethylene-vinyl acetate copolymer, hydroxyethyl acrylate, and dicumyl peroxide in a mixer according to a mass ratio of 100:(2-7):(0.12-0.46), and then performing melt grafting in a single screw extruder at a melt temperature of 160-170° C. and a screw speed of 30-50 r / min, and extruding to obtain hydroxyethyl acrylate grafted EVA.

[0015] Preferably, the preparation method of the anti-fall antibacterial foam insole comprises: placing ethylene-vinyl acetate copolymer, hydroxyl-containing polyquaternary ammonium salt, hydroxyethyl acrylate grafted EVA, terminal isocyanate polyurethane, and additives in an internal mixer, kneading for 10-15 minutes at 110-120°C, then adding a cross-linking agent and a foaming agent, and kneading for 3-5 minutes; placing the materials in an open mixer for internal kneading, making a triangular bag, thinning, cooling and sheeting; and finally molding in a flat vulcanizer for 40-60 minutes, controlling the pressure to 12-18 MPa and the temperature to 160-170°C to obtain the anti-fall antibacterial foam insole.

[0016] Preferably, a dot protrusion matrix is ​​provided on the lower surface of the anti-fall and antibacterial foam insole to increase the friction between the insole and the sole and improve the anti-slip and anti-fall performance.

[0017] The technical effect produced by the present invention is that: the present invention carries out quaternization reaction on 1,3-dichloro-2-propanol and N,N-bis[2-(dimethylamino)ethyl]terephthalamide, and polymerizes to obtain a hydroxyl-containing polyquaternary ammonium salt.

[0018] The present invention uses ethylene-vinyl acetate copolymer EVA as the basis of foaming insole material, adds hydroxyl-containing polyquaternary ammonium salt, hydroxyethyl acrylate grafted EVA, terminal isocyanate polyurethane, foaming agent, crosslinking agent and the like. In high-temperature mixing and molding process, the hydroxyl of hydroxyl-containing polyquaternary ammonium salt and hydroxyethyl acrylate grafted EVA reacts with the terminal isocyanate group of polyurethane, so that the three form a chemically crosslinked hybrid system, the crosslinked hybrid system contains EVA component, which can play the role of compatilizer, improves the compatibility between the crosslinked hybrid system and the ethylene-vinyl acetate copolymer EVA substrate, and the polyurethane has good toughness in the crosslinked hybrid system, and has good toughening effect on the EVA insole material. Simultaneously, the molecular main chain of the hydroxyl-containing polyquaternary ammonium salt contains rigid benzene ring, which is conducive to improving the strength of the EVA insole material, and the insole material is shown in higher tear strength, tensile strength and elongation at break under synergistic effect.

[0019] The invention adds hydroxyl-containing polyquaternary ammonium salt to the EVA foam insole material, and the polyquaternary ammonium salt contains hydrophilic groups such as hydroxyl, quaternary ammonium salt cation and amide group, which can improve the hydrophilicity of the insole material and help improve the moisture absorption and moisture permeability of the insole material. In addition, the main chain of the molecule contains a large number of antibacterial quaternary ammonium salt groups, and exhibits a high inhibition zone and antibacterial and bactericidal effect on bacteria and molds such as Staphylococcus aureus, Candida albicans, Penicillium, Aspergillus niger, etc., and significantly improves the antibacterial and mildew-proof performance of the foam insole material.

[0020] The present invention arranges a dot protrusion matrix on the lower surface of the anti-fall antibacterial foam insole to increase the friction between the insole and the sole and improve the anti-slip and anti-fall performance. DETAILED DESCRIPTION

[0021] The following embodiments of the present invention are further described in detail in conjunction with the examples. The detailed description of the following embodiments is used to illustrate the principle of the present invention, but cannot be used to limit the scope of the present invention, that is, the present invention is not limited to the described embodiments.

[0022] Example 1

[0023] (1) Add 15 mmol terephthaloyl chloride, 30 mmol N,N-dimethylethylenediamine, and 33 mmol pyridine to 30 mL tetrahydrofuran, and stir at room temperature to react for 6 hours. Rotary evaporate the solution, separate by silica gel column chromatography, and elute with a solution of ethyl acetate and petroleum ether to obtain N,N-bis[2-(dimethylamino)ethyl]terephthalamide.

[0024] (2) Add 20 mmol 1,3-dichloro-2-propanol and 20 mmol N,N-bis[2-(dimethylamino)ethyl]terephthalamide to 40 mL of isopropanol, stir and condense under reflux at 85°C for 60 h, rotary evaporate the solution, wash with acetone, and dry to obtain a hydroxyl-containing polyquaternary ammonium salt.

[0025] (3) Dry 30 mmol of polyethylene glycol 1000 to remove water, then mix it with 66 mmol of diphenylmethane-4,4'-diisocyanate, react at 65°C for 3 hours in a nitrogen atmosphere, and cool to obtain terminal isocyanate polyurethane.

[0026] (4) 50 g of ethylene-vinyl acetate copolymer, 1 g of hydroxyethyl acrylate, and 0.06 g of diisopropylbenzene peroxide were mixed in a mixer, and then melt-grafted in a single-screw extruder at a melt temperature of 170° C. and a screw speed of 30 r / min to obtain hydroxyethyl acrylate-grafted EVA.

[0027] (5) 1000 g of ethylene-vinyl acetate copolymer, 10 g of hydroxyl-containing polyquaternary ammonium salt, 6 g of hydroxyethyl acrylate grafted EVA, 8 g of terminal isocyanate polyurethane, 5.3 g of zinc stearate and 6.2 g of stearic acid as additives are placed in an internal mixer and kneaded at 110° C. for 15 min. Then, 12 g of diisopropylbenzene peroxide as a cross-linking agent and 44 g of azodicarbonamide as a foaming agent are added and kneaded for 3 min. The materials are placed in an open mixer for internal kneading, triangularly packaged, thinly passed, and cooled to form a sheet. Finally, the materials are molded in a flat vulcanizer for 60 min, with the pressure controlled at 12 MPa and the temperature at 170° C., and a dot protrusion matrix is ​​set on the lower surface of the foamed insole to obtain a fall-resistant and antibacterial foamed insole material.

[0028] Example 2

[0029] (1) Add 15 mmol terephthaloyl chloride, 33 mmol N,N-dimethylethylenediamine, and 33 mmol pyridine to 40 mL tetrahydrofuran, stir and react at room temperature for 6 hours, rotary evaporate the solution, separate by silica gel column chromatography, and elute with a solution of ethyl acetate and petroleum ether to obtain N,N-bis[2-(dimethylamino)ethyl]terephthalamide.

[0030] (2) Add 20 mmol 1,3-dichloro-2-propanol and 24 mmol N,N-bis[2-(dimethylamino)ethyl]terephthalamide to 50 mL of isopropanol, stir and reflux at 85°C for 48 hours, rotary evaporate the solution, wash with acetone, and dry to obtain a hydroxyl-containing polyquaternary ammonium salt.

[0031] (3) Dry 30 mmol of polyethylene glycol 1000 to remove water, then mix it with 63 mmol of isophorone diisocyanate, react it at 70°C in a nitrogen atmosphere for 2 hours, and cool it to obtain terminal isocyanate polyurethane.

[0032] (4) 50 g of ethylene-vinyl acetate copolymer, 2.2 g of hydroxyethyl acrylate and 0.15 g of diisopropylbenzene peroxide were mixed in a mixer, and then melt-grafted in a single-screw extruder at a melt temperature of 160° C. and a screw speed of 50 r / min to obtain hydroxyethyl acrylate-grafted EVA.

[0033] (5) 1000 g of ethylene-vinyl acetate copolymer, 40 g of hydroxyl-containing polyquaternary ammonium salt, 25 g of hydroxyethyl acrylate grafted EVA, 36 g of terminal isocyanate polyurethane, 6.7 g of zinc stearate and 8.3 g of stearic acid as additives are placed in an internal mixer and kneaded at 120° C. for 15 min. Then, 12 g of diisopropylbenzene peroxide as a cross-linking agent and 40 g of azodicarbonamide as a foaming agent are added and kneaded for 5 min. The materials are placed in an open mixer for internal kneading, triangularly packaged, thinly passed, and cooled to form a sheet. Finally, the materials are molded in a flat vulcanizer for 60 min, with the pressure controlled at 18 MPa and the temperature at 160° C., and a dot protrusion matrix is ​​set on the lower surface of the foamed insole to obtain a fall-resistant and antibacterial foamed insole material.

[0034] Example 3

[0035] (1) Add 15 mmol terephthaloyl chloride, 27 mmol N,N-dimethylethylenediamine, and 30 mmol pyridine to 30 mL tetrahydrofuran, and stir at room temperature to react for 10 hours. Rotary evaporate the solution, separate by silica gel column chromatography, and elute with a solution of ethyl acetate and petroleum ether to obtain N,N-bis[2-(dimethylamino)ethyl]terephthalamide.

[0036] (2) Add 20 mmol 1,3-dichloro-2-propanol and 16 mmol N,N-bis[2-(dimethylamino)ethyl]terephthalamide to 40 mL of isopropanol, stir and reflux at 80°C for 60 h, rotary evaporate the solution, wash with acetone, and dry to obtain a hydroxyl-containing polyquaternary ammonium salt.

[0037] (3) Dry 30 mmol polyethylene glycol 1000 to remove water, then mix it with 66 mmol toluene-2,4-diisocyanate, react at 70°C for 2 h in a nitrogen atmosphere, and cool to obtain terminal isocyanate polyurethane.

[0038] (4) 50 g of ethylene-vinyl acetate copolymer, 3.5 g of hydroxyethyl acrylate and 0.23 g of diisopropylbenzene peroxide were mixed in a mixer, and then melt-grafted in a single-screw extruder at a melt temperature of 165° C. and a screw speed of 50 r / min to obtain hydroxyethyl acrylate-grafted EVA.

[0039] (5) 1000 g of ethylene-vinyl acetate copolymer, 80 g of hydroxyl-containing polyquaternary ammonium salt, 50 g of hydroxyethyl acrylate grafted EVA, 70 g of terminal isocyanate polyurethane, 4.6 g of zinc stearate and 3.4 g of stearic acid as additives are placed in an internal mixer and kneaded at 120° C. for 10 min. Then, 17 g of cross-linking agent diisopropyl peroxide and 55 g of foaming agent azodicarbonamide are added and kneaded for 3 min. The materials are placed in an open mixer for internal kneading, triangularly packaged, thinly passed, and cooled to form a sheet. Finally, the materials are molded in a flat vulcanizer for 40 min, with the pressure controlled at 15 MPa and the temperature at 170° C., and a dot protrusion matrix is ​​set on the lower surface of the foamed insole to obtain a fall-resistant and antibacterial foamed insole material.

[0040] Comparative Example 1

[0041] (1) 1000 g of ethylene-vinyl acetate copolymer, 5.3 g of zinc stearate and 6.2 g of stearic acid as additives are placed in an internal mixer and kneaded at 110° C. for 15 min. Then, 12 g of diisopropylbenzene peroxide as a cross-linking agent and 44 g of azodicarbonamide as a foaming agent are added and kneaded for 3 min. The materials are placed in an open mixer for internal kneading, triangularly packaged, thinly passed, and cooled to form a sheet. Finally, the materials are molded in a flat vulcanizer for 60 min, with the pressure controlled at 12 MPa and the temperature at 170° C., and a dot protrusion matrix is ​​set on the lower surface of the foamed insole to obtain an anti-fall and antibacterial foamed insole material.

[0042] Comparative Example 2

[0043] (1) 1000 g of ethylene-vinyl acetate copolymer, 6 g of hydroxyethyl acrylate grafted EVA, 8 g of terminal isocyanate polyurethane, 5.3 g of zinc stearate and 6.2 g of stearic acid as additives are placed in an internal mixer and kneaded at 110° C. for 15 min, then 12 g of diisopropylbenzene peroxide as a cross-linking agent and 44 g of azodicarbonamide as a foaming agent are added and kneaded for 3 min; the materials are placed in an open mixer for internal kneading, triangularly packaged, thinly passed, and cooled to form a sheet; finally, molded in a flat vulcanizer for 60 min, the pressure is controlled to be 12 MPa, and the temperature is 170° C., and a dot protrusion matrix is ​​set on the lower surface of the foamed insole to obtain an anti-fall and antibacterial foamed insole material.

[0044] Comparative Example 3

[0045] (1) 1000 g of ethylene-vinyl acetate copolymer, 10 g of hydroxyl-containing polyquaternary ammonium salt, 8 g of terminal isocyanate polyurethane, 5.3 g of zinc stearate and 6.2 g of stearic acid as additives are placed in an internal mixer and kneaded at 110° C. for 15 min, then 12 g of diisopropylbenzene peroxide as a cross-linking agent and 44 g of azodicarbonamide as a foaming agent are added and kneaded for 3 min; the materials are placed in an open mixer for internal kneading, triangularly packaged, thinly passed, and cooled to form a sheet; finally, molded in a flat vulcanizer for 60 min, with the pressure controlled at 12 MPa and the temperature at 170° C., and a dot protrusion matrix is ​​set on the lower surface of the foamed insole to obtain an anti-fall and antibacterial foamed insole material.

[0046] Comparative Example 4

[0047] (1) 1000 g of ethylene-vinyl acetate copolymer, 10 g of hydroxyl-containing polyquaternary ammonium salt, 6 g of hydroxyethyl acrylate grafted EVA, 5.3 g of zinc stearate and 6.2 g of stearic acid as additives are placed in an internal mixer and kneaded at 110° C. for 15 min, then 12 g of diisopropylbenzene peroxide as a cross-linking agent and 44 g of azodicarbonamide as a foaming agent are added and kneaded for 3 min; the materials are placed in an open mixer for internal kneading, triangularly packaged, thinly passed, and cooled to form a sheet; finally, molded in a flat vulcanizer for 60 min, with the pressure controlled at 12 MPa and the temperature at 170° C., and a dot protrusion matrix is ​​set on the lower surface of the foamed insole to obtain an anti-fall and antibacterial foamed insole material.

[0048] Comparative Example 5

[0049] (1) Add 20 mmol 1,3-dichloropropane and 20 mmol N,N-bis[2-(dimethylamino)ethyl]terephthalamide to 40 mL of isopropanol, stir and reflux at 85°C for 60 hours, rotary evaporate the solution, wash with acetone, and dry to obtain a polyquaternary ammonium salt.

[0050] (2) 1000 g of ethylene-vinyl acetate copolymer, 10 g of polyquaternary ammonium salt, 6 g of hydroxyethyl acrylate grafted EVA, 8 g of terminal isocyanate polyurethane, 5.3 g of zinc stearate and 6.2 g of stearic acid as additives are placed in an internal mixer and kneaded at 110° C. for 15 min. Then, 12 g of diisopropylbenzene peroxide as a cross-linking agent and 44 g of azodicarbonamide as a foaming agent are added and kneaded for 3 min. The materials are placed in an open mixer for internal kneading, triangularly packaged, thinly passed, and cooled to form a sheet. Finally, the materials are molded in a flat vulcanizer for 60 min, with the pressure controlled at 12 MPa and the temperature at 170° C., and a dot protrusion matrix is ​​set on the lower surface of the foamed insole to obtain a fall-resistant and antibacterial foamed insole material.

[0051] The tensile strength and elongation at break were tested using a universal tensile testing machine according to GB / T 6344-2008. The tear strength of the insole material was tested according to GB / T 10808-2006.

[0052] The water contact angle on the surface of the insole material was tested using a contact angle meter. Each sample was tested 5 times and the average value was taken.

[0053] Table 1 Insole material performance test

[0054]

[0055]

[0056] As shown in Table 1, compared with Comparative Example 1, hydroxy-containing polyquaternary ammonium salt is added in the EVA insole material of embodiment 1-3, hydroxyethyl acrylate grafted EVA, terminal isocyanate polyurethane, in high temperature mixing and molding process, hydroxy-containing polyquaternary ammonium salt, the hydroxyl of hydroxyethyl acrylate grafted EVA reacts with the terminal isocyanate group of polyurethane, three are formed into a chemically crosslinked hybrid system, the cross-linked hybrid system contains EVA component, the effect of compatilizer can be played, the compatibility between cross-linked hybrid system and ethylene-vinyl acetate copolymer (EVA) is improved, polyurethane has good toughness in the cross-linked hybrid system, the EVA insole material has a good toughening effect, the molecular backbone of hydroxy-containing polyquaternary ammonium salt contains rigid benzene ring simultaneously, it is conducive to improving the intensity of EVA insole material, under synergistic effect, the insole material is shown higher tear strength, tensile strength and elongation at break. And hydroxy-containing polyquaternary ammonium salt contains hydroxyl, hydrophilic groups such as quaternary ammonium salt cation and amide group, it is possible to improve the hydrophilicity of the insole material, it is conducive to improving the moisture absorption and moisture permeability of the insole material.

[0057] Compared with Example 1, Comparative Example 2 does not add hydroxyl-containing polyquaternary ammonium salt, and its tear strength and tensile strength are lower than those of Example 1, and its water contact angle is larger, and its hydrophilic property is poor.

[0058] Compared with Example 1, Comparative Example 3 does not add hydroxyethyl acrylate grafted EVA. Although the hydroxyl-containing polyquaternary ammonium salt and the terminal isocyanate polyurethane can undergo a cross-linking reaction, the formed cross-linked hybrid system does not contain an EVA structure, resulting in poor compatibility between the cross-linked hybrid system and the EVA foam material, poor reinforcement and toughening effects, and tear strength, tensile strength and elongation at break are significantly lower than those in Example 1.

[0059] Compared with Example 1, Comparative Example 4 did not add terminal isocyanate polyurethane, and could not undergo cross-linking reaction with hydroxyl-containing polyquaternary ammonium salt and hydroxyethyl acrylate grafted EVA, resulting in hydroxyethyl acrylate grafted EVA not playing the role of a compatibilizer, and did not improve the compatibility between the hydroxyl-containing polyquaternary ammonium salt and the EVA foam material. The tear strength, tensile strength and elongation at break were significantly lower than those in Example 1.

[0060] Compared with Example 1, Comparative Example 5 uses 1,3-dichloropropane to react with N,N-bis[2-(dimethylamino)ethyl]terephthalamide, and the obtained polyquaternary ammonium salt does not contain hydroxyl groups and cannot undergo cross-linking reaction with terminal isocyanate polyurethane and hydroxyethyl acrylate grafted EVA, resulting in poor compatibility of the polyquaternary ammonium salt with the EVA foam material, and the tear strength, tensile strength and elongation at break are lower than those in Example 1.

[0061] Staphylococcus aureus, Candida albicans, Penicillium and Aspergillus niger were used as the test bacteria and molds. The antibacterial properties of the insole materials against bacteria and molds were tested using the inhibition zone diameter method.

[0062] The insole material was pressed into a film sample with a thickness of 1 mm, 0.2 mL of activated bacteria or mold liquid was applied to the surface of the culture medium, and then cultured in a constant temperature incubator. After culture, the diameter of the inhibition zone was measured. Each group of samples was tested 3 times and the average value was taken.

[0063] The concentration of activated bacterial solution of Staphylococcus aureus and Candida albicans was 10 7 cfu / mL, the culture medium was beef extract peptone, the culture temperature was 37°C, and the culture time was 24h.

[0064] The culture medium for Penicillium and Aspergillus niger is potato culture medium. The spore concentration of the mold liquid is 10 6 / mL, the culture temperature was 28℃, and the time was 48h.

[0065] Table 2 Antibacterial and anti-mildew performance test of insole materials

[0066]

[0067] As can be seen from Table 2, Examples 1-3 and Comparative Examples 3-4 added hydroxyl-containing polyquaternary ammonium salts, and Comparative Example 5 added polyquaternary ammonium salts, whose molecular main chains contain a large number of antibacterial quaternary ammonium salt groups, and exhibited high inhibition zones and antibacterial and bactericidal effects on bacteria and molds such as Staphylococcus aureus, Candida albicans, Penicillium, and Aspergillus niger, thereby significantly improving the antibacterial and mildew-proof properties of the EVA foam insole material.

[0068] The above are only embodiments of the present application and are not limited to the present application. For those skilled in the art, the present application may have various changes and variations without departing from the scope of the present invention. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.

Claims

1. A fall-proof and antibacterial foam insole, characterized in that: The invention comprises the following components in parts by weight: 100 parts of ethylene-vinyl acetate copolymer, 1-8 parts of hydroxyl-containing polyquaternary ammonium salt, 0.6-5 parts of hydroxyethyl acrylate grafted EVA, 0.8-7 parts of terminal isocyanate polyurethane, 4-5.5 parts of foaming agent, 0.8-1.5 parts of auxiliary agent, and 1.2-1.7 parts of crosslinking agent; The preparation method of the hydroxyl-containing polyquaternary ammonium salt comprises: adding 1,3-dichloro-2-propanol and N,N-bis[2-(dimethylamino)ethyl]terephthalamide in a molar ratio of 1:(0.8-1.2) into isopropanol, stirring to react, rotary evaporating the solution, washing with acetone, and drying to obtain the hydroxyl-containing polyquaternary ammonium salt.

2. The anti-fall and antibacterial foam insole according to claim 1, characterized in that: The reaction was refluxed at 80-85°C for 48-60h.

3. The anti-fall and antibacterial foam insole according to claim 1, characterized in that: The preparation method of N,N-bis[2-(dimethylamino)ethyl]terephthalamide comprises: adding terephthaloyl chloride, N,N-dimethylethylenediamine and pyridine in a molar ratio of 1:(1.8-2.2):(2-2.2) to tetrahydrofuran, stirring and reacting at room temperature for 6-10 hours, rotary evaporating the solution, separating by silica gel column chromatography, and eluting with a solution of ethyl acetate and petroleum ether to obtain N,N-bis[2-(dimethylamino)ethyl]terephthalamide.

4. The anti-fall and antibacterial foam insole according to claim 1, characterized in that: The preparation method of the isocyanate-terminated polyurethane comprises: drying and removing water from polyethylene glycol, then mixing with diisocyanate in a molar ratio of 1:(2.1-2.2), reacting at 65-70° C. for 2-3 hours in a nitrogen atmosphere, and cooling to obtain the isocyanate-terminated polyurethane.

5. The anti-fall and antibacterial foam insole according to claim 4, characterized in that: The diisocyanate is isophorone diisocyanate, toluene-2,4-diisocyanate or diphenylmethane-4,4'-diisocyanate.

6. The anti-fall and antibacterial foam insole according to claim 1, characterized in that: The foaming agent is azodicarbonamide, and the cross-linking agent is dicumyl peroxide.

7. The anti-fall and antibacterial foam insole according to claim 1, characterized in that: The auxiliary agent includes zinc stearate, stearic acid or a combination thereof.

8. The anti-fall and antibacterial foam insole according to claim 1, characterized in that: The preparation method of hydroxyethyl acrylate grafted EVA comprises: mixing ethylene-vinyl acetate copolymer, hydroxyethyl acrylate and dicumyl peroxide in a mixer according to a mass ratio of 100:(2-7):(0.12-0.46), and then performing melt grafting in a single screw extruder at a melt temperature of 160-170° C. and a screw speed of 30-50 r / min, and extruding to obtain hydroxyethyl acrylate grafted EVA.

9. A method for preparing the anti-fall antibacterial foam insole according to any one of claims 1 to 8, characterized in that: The preparation method comprises: placing ethylene-vinyl acetate copolymer, hydroxyl-containing polyquaternary ammonium salt, hydroxyethyl acrylate grafted EVA, terminal isocyanate polyurethane and additives in an internal mixer, kneading for 10-15 minutes at 110-120° C., then adding a crosslinking agent and a foaming agent, and kneading for 3-5 minutes; placing the materials in an open mixer for internal kneading, making triangular packages, thinning, cooling and forming sheets; and finally molding in a flat vulcanizer for 40-60 minutes, controlling the pressure to be 12-18 MPa and the temperature to be 160-170° C., to obtain a fall-resistant and antibacterial foamed insole.

10. The anti-fall and antibacterial foam insole obtained by the preparation method according to claim 9, characterized in that: A dot protrusion matrix is ​​arranged on the lower surface of the anti-fall antibacterial foam insole to increase the friction between the insole and the sole.

Citation Information

Patent Citations

  • Method for producing antimicrobial plastics for injection molded parts

    CN118006032B

  • Method for preparing quaternary ammonium salt

    CN101050182A

  • Bi-color antibacterial EVA footwear and preparation method thereof

    CN104861279A

  • Composition for foaming material with high rebound resilience and preparation method thereof

    CN107151373A

  • Antibacterial foaming insole and preparation method thereof

    CN107674293A

Cited By

  • Shoe material master batch based on coffee grounds and preparation method thereof

    CN120383828A

  • Bacteriostatic and deodorant EVA foam material and preparation method thereof

    CN122037366A

  • An antibacterial and deodorizing EVA foam material and its preparation method

    CN122037366B